PENGARUH KUALITAS PRODUK TERHADAP JUMLAH NASABAH PT. BPR EKA BUMI ARTHA LAMPUNG - Yudiana Sari (Fakultas Teknik Universitas Tulang Bawang Lampung, 2017)
The object of this research is PT. BPR Eka Bumi Artha Lampung. One concern in the field of economic and social organization of society embodied in the form of the establishment of the Bank, so that at the start of operations of PT. BPR Eka Bumi Artha Lampung more social character. The problem under study is to determine the quality of products on the number of customers of PT. BPR Eka Bumi Artha Lampung because the number of customers of PT. BPR Eka Bumi Artha Lampung declining. The method used is the literature research, interviews and questionnaires related to product quality and its effect on the number of customers of PT. BPR Eka Bumi Artha Lampung. The results showed that the calculation of product moment correlation and coefficient of determination (KD), it can be concluded that the seven dimensions of perception of product quality (performance, survive in the hearts of customers, service, reliability, product characteristics, compliance with specifications, results) overall influence positively to the number of customers of PT. BPR Eka Bumi Artha Lampung with a value of 32.49%. Hypothesis tests were carried out, can be concluded that the quality of the product has a positive influence on the decision to become customers of PT. BPR Eka Bumi Artha Lampung. This is evident from the results of hypothesis testing to see that t = 6.6 t greater than t table for n = 92, at the 95% confidence level that is equal to 1.658. Based on a qualitative analysis of questionnaires submitted, it can be concluded that the decision to become customers of PT. BPR Eka Bumi Artha Lampung to the product formed from the seven dimensions of quality overall is considered good with an average value of 352.64. Keywords: Quality, Product, Customer, Product Moment Correlation, Coefficient of Determination